The European Council and the European Union’s external activities. Forming relations with eastern neighbors - Jańczak, Jarosław (Przegląd Politologiczny, 2018)
The modification process of the European Union’s institutional order appears to be permanent. One of the elements of this tendency is the position of the European Council, which is especially interesting in the field of stimulating external EU activities. The aim of this analysis is to explore the EC’s engagement in initiating foreign relations, taking the eastern neighborhood as an example. The paper reviews the European Council’s meetings in the period of 2008–2016, concluding that the EC actively responded to external challenges and created a political impetus for the actions of other institutions. The internal debate initiated by the member states from Central and Eastern Europe resulted in the formulation of the Eastern Partnership initiative that the European Council approved and adopted, giving it a political impetus within the European Union. This caused a specific reaction in the neighborhood. The process of association of some eastern partners was accompanied by the need to deal with the challenging response from Russia, which resorted, among other things, to military measures. The European Council’s involvement in external actions in the East became a self-deepening process with a changing profile and priorities.